Determining the Degree of Fiscal Dominance and its Implication on the Conduct of Monetary Policy in Nigeria - Omo-Ikirodah, Beatrice Onawunreyi; Afolabi, Joseph Olarewaju (Olsztyn Economic Journal, 2022)
This study determines the degree of fiscal dominance and its implication on the conduct of monetary policy in Nigeria. It adopts the Dynamic Ordinary Least Square (DOLS) estimation techniques and covers the periods of 1980 to 2020. The regression result shows an estimated coefficient of 0.77, which indicate a high degree of fiscal dominance in the country. In the same vein, the estimated coefficient was compared with the average value of the consumer price index and interest rate in the economy, and it was discovered that high degree of fiscal dominance corresponds with high consumer price index and interest rate in the economy. Flowing from the findings, it is concluded that there is high degree of fiscal dominance in Nigeria, and this has implication on the conduct of monetary policies in thecountry. The degree of fiscal dominance in the country is likely one of the factors responsible for high prices in the country. It was recommended that The Nigerian government should focus on widening the domestic revenue mobilization base of the country. This would include expanding the tax base, setting up appropriate mechanism to generate more revenue from fines, fees and licenses, providing a conducive environment for remittances inflow into the country. The Central bank should limit their finances of government expenditure to 10 percent of previous year’s revenue as suggested by the World Bank. They should limit their borrowings to capital project, such that such project can boast aggregate supply and normalize average prices in the economy.